Evaluating the persistence and stability of a DNA-barcoded microbial system in a mock home environment. Issue 1 (12th August 2022) - McDonald, Nathan D; Rhea, Katherine A; Davies, John P; Zacharko, Julie L; Berk, Kimberly L; Buckley, Patricia E
Abstract: Recent advancements in engineered microbial systems capable of deployment in complex environments have enabled the creation of unique signatures for environmental forensics operations. These microbial systems must be robust, able to thrive in specific environments of interest and contain molecular signatures, enabling the detection of the community across conditions. Furthermore, these systems must balance biocontainment concerns with the stability and persistence required for environmental forensics. Here we evaluate the stability and persistence of a recently described microbial system composed of germination-deficient Bacillus subtilis and Saccharomyces cerevisiae spores containing nonredundant DNA barcodes in a controlled simulated home environment. These spore-based microbial communities were found to be persistent in the simulated environment across 30-day periods and across multiple surface types. To improve the repeatability and reproducibility in detecting the DNA barcodes, we evaluated several spore lysis and sampling processes paired with Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) -CRISPR-associated proteins (Cas) detection (Sherlock). Finally, having optimized the detectability of the spores, we demonstrate that we can detect the spores transferring across multiple material types. Together, we further demonstrate the utility of a recently described microbial forensics system and highlight the importance of independent validation and verification of synthetic biology tools and applications. Graphical Abstract